Images of childhood - Wyver, Shirley R.; Whiteman, Peter (Children and childhoods, 2012)
Decisions relating to children's lives, including formation of policies about children and young people, advocating for children's rights, educational instruction and parenting, all depend on images of children and childhoods. Nonetheless, prevailing images of childhood are not often subject to critique. Images of Childhood offers an examination of public images of childhood in the context of research findings. Authors from a wide range of disciplines, including early childhood, psychology, ...